Prevalence of Persistent Olfactory Disorders in Patients With COVID-19: A Psychophysical Case-Control Study With 1-Year Follow-up. (July 2022) - Vaira, Luigi Angelo; Salzano, Giovanni; Le Bon, Serge Daniel; Maglio, Angelantonio; Petrocelli, Marzia; Steffens, Younes; Ligas, Enrica; Maglitto, Fabio; Lechien, Jerome R.; Saussez, Sven; Vatrella, Alessandro; Salzano, Francesco Antonio; et al.
The purpose of this multicenter case-control study was to evaluate a group of patients at least 1 year after coronavirus disease 2019 (COVID-19) with Sniffin' Sticks tests and to compare the results with a control population to quantify the potential bias introduced by the underlying prevalence of olfactory dysfunction (OD) in the general population. The study included 170 cases and 170 controls. In the COVID-19 group, 26.5% of cases had OD (anosmia in 4.7%, hyposmia in 21.8%) versus 3.5% in the control group (6 cases of hyposmia). The TDI score (threshold, discrimination, and identification) in the COVID-19 group was significantly lower than in the control group (32.5 [interquartile range, 29-36.5] vs 36.75 [34-39.5], P < .001). The prevalence of OD was significantly higher in the COVID-19 group, confirming that this result is not due to the underlying prevalence of OD in the general population.